Measurement of Reactive Oxygen Species, Reactive Nitrogen Species, and Redox-Dependent Signaling in the Cardiovascular System: A Scientific Statement From the American Heart Association. Issue 5 (19th August 2016) - Griendling, Kathy K.; Touyz, Rhian M.; Zweier, Jay L.; Dikalov, Sergey; Chilian, William; Chen, Yeong-Renn; Harrison, David G.; Bhatnagar, Aruni
Abstract : Reactive oxygen species and reactive nitrogen species are biological molecules that play important roles in cardiovascular physiology and contribute to disease initiation, progression, and severity. Because of their ephemeral nature and rapid reactivity, these species are difficult to measure directly with high accuracy and precision. In this statement, we review current methods for measuring these species and the secondary products they generate and suggest approaches for measuring redox status, oxidative stress, and the production of individual reactive oxygen and nitrogen species. We discuss the strengths and limitations of different methods and the relative specificity and suitability of these methods for measuring the concentrations of reactive oxygen and reactive nitrogen species in cells, tissues, and biological fluids. We provide specific guidelines, through expert opinion, for choosing reliable and reproducible assays for different experimental and clinical situations. These guidelines are intended to help investigators and clinical researchers avoid experimental error and ensure high-quality measurements of these important biological species.